The Art of Living is Living with the Art; Is it Essential that Bapedi People Are Able to Live with and Embrace the Past? Yes, Definitely - Lebaka, Morakeng Edward Kenneth (European Journal of Social Science Education and Research, 2021)
For many centuries, music has been used in different indigenous African religious rituals as part of communal and personal religious rites. In the Bapedi society, songs accompany every phase of the divination process and, also any other task which they perform communally, for example, ancestor veneration. The purpose of this study was to investigate how Bapedi traditional healers and their trainees create imprecatory songs, as well as their societal value. The main questions the study addressed are: a) how do Bapedi traditional healers create imprecatory songs; and b) what is the societal value of these songs in the Bapedi culture. The study used a naturalistic approach and the methods of data collection were video recordings of cultural and religious rituals, interviews and observations. The study has revealed that in the Bapedi society like in other African societies, narratives in imprecatory songs can be classified broadly into three, namely: segmental narrative; incremental cycle and multiple recycle forms. The results have also shown that Bapedi imprecation songs serve various functions such as education, upholding and promoting morals and customs through advice, insults and mockery. This paper is submitted for consideration for the ICMS XXV, 25th International Conference entitled “Ideas and Research on Recent Issues”; University of Southern California.
Keywords: Bapedi society, imprecatory Psalm-like texts, Bapedi culture, divination process, Bapedi traditional healers